Konjuktionale Koordination in Predigten und politischen Reden Dargestellt an Belegen aus dem Russischen - Kusse, Holger (Specimina philologiae Slavicae, 1998)
The originality of the dissertation can be seen first and foremost in the fact that the author "spectralized" the problem of conjunctural meaning, i. that, starting from a general systemic meaning or function, he has detected and analyzed both modes of use (that is, specific, derivable text meanings) and argumentative functions (ie, textual meanings of a higher degree). The special significance of the work has not only been determined by the three expert reviewers from Slavic studies; The additional expert opinion from theology has also confirmed to the Slavist and theologian Holger Kuße that he worked theologically clean.